Crohn’s disease triggering ileoileal intussusception in an adult - Gnanadev, Praveen; N. K., Mukunda; Taluru, Hariprasad Ramachandra Naidu; Krishnappa, Rohit; N. S., Vinayaka; Damodaran, Geethu; G., Suhas (International Surgery Journal, 2021)
Intussusception is defined as the telescoping of a segment of the gastrointestinal tract (intussusceptum) into an immediately adjacent distal bowel (intussuscipiens), causing venous congestion, edema, and blood supply reduction. Adult intussusception is a rare entity which can be with or without lead-point. Cases without lead-point frequently occurs in children or adults with celiac disease and Crohn’s disease and with lead point is caused by an underlying neoplasm, benign or malignant frequently presenting with bowel obstruction and acute abdomen. A 41-years-old male presented to our outpatient clinic with a history of recurrent abdominal pain. The clinical presentation and CT scan findings led to the diagnosis of ileoileal intussusception. Subsequently he underwent laparotomy which revealed an ileal intussusception, which was investigated and was found to be of Crohn’s etiology.